ANALISIS SENGKETA HARTA WARISAN MENURUT AL-QUR’AN DAN AS-SUNNAH (Studi Putusan Pengadilan Agama Kisaran Studi Kasus No.353/Pdt./2010/PA.Kis) - Nurwandi, Andri; Syam, Nur Fadhilah (Al-I'jaz: Jurnal Kewahyuan Islam, 2021)
ABSTRACTFaraidh law if implemented honestly and correctly, then the fear of the negative impact of the influence of the property left behind by the dead can be minimized. Faraidh law, in addition to the right of inheritance can be returned properly to those who have the right, also very basic is to make the family concerned live peacefully as before. The purpose of this study is to determine the concept of inheritance according to the Qur'an and As-Sunnah, to find out the basic considerations of the judges of the Kisaran Religious Court in deciding cases and how to settle inheritance No.353/Pdt.G/2010/PA.Kis. The author's research method by collecting data through the existing literature is in accordance with this research study, that the research conducted is library research. Furthermore, the author uses qualitative methods and data analysis, meaning that the problem will be presented qualitatively and then analyzed and in this thesis the author analyzes the judge's decision. From the results of the study the authors found that the problem in this case is the inheritance dispute caused by the remaining assets (tirkah) and grants. In the case of mal waris inheritance, the judge must really consider whether the conditions specified in the Qur'an, the Sunnah, the Shari'a and the law are appropriate or not, the reasons that cause the mal heir inheritance dispute must also be considered. This can be done in the examination in the trial and also in the evidentiary process.Keywords: dispute, inheritance, al-qur'an and as-sunnah